Pengaruh Shopping Lifestyle Dan Fashion Involvement Terhadap Impulse Buying (Studi Kasus Pada Konsumen Toko Mantan Karyawan Kota Bengkulu) - Ade Tiara Yulinda; Rike Rahmawati; Heldi Sahputra (UNIVED Press, 2022)
The advance of this modern era is triggered the increasing of fashion trends, which make the need for goods and services in the fashion sector is more increasing and vary. The problem faced, business people are required to provide a variety of fashion that is taste of consumers. By paying attention to shopping lifestyle and fashion involvement business people can attract consumers to do impulse buying. This study aims to analyze the effect of shopping lifestyle and fashion involvement on impulse buying consumers of Mantan Karyawan shop’s in Bengkulu city. The research used a quantitative with associative quantitative approach. Sampling of this research used purposive sampling technique with sample of 150 responden. Data was collected through multiple linier regression by using SPSS 24 tool. The results of research showed that there was an effect shopping lifestyle and fashion involvement on impulse buying. The coefficient of determination, which can be seen of R square = 0.786. This showed that shopping lifestyle and fashion involvement affect impulse buying by 78.6 %, while the remaining 21.4% can be explained by other variabels not included in this study. Other, data also showed the effect of shopping lifestyle and fashion involvement on impulse buying, this can be seen from the results of t_count, which was greater that t_table, this can be concluded that Ha is accepted and H0 is rejected. Partially and simultaneously, this study sum up that shopping lifestyle and fashion involvement affect the impulse buying consumers of Mantan Karyawan shops in Bengkulu City.